Effect of FADH2 on the hydrolytic activity of mitochondrial ATPase (Revista Española de Fisiología, 1993)
FADH2 affected mitochondrial ATPase activity of both F1 and the membrane bound enzyme. F1-ATPase activity increased in its presence, whereas that of the membrane bound enzyme decreased. These effects were more marked at low substrate concentrations. The inhibition of membrane bound ATPase activity was not reversed by ADP. However, the simultaneous presence of free ATP and FADH2 produced a stimulation of the membrane bound enzyme activity. The varying effect of FADH2 on the membrane bound ATPase activity, depending on ATP concentration, could be the expression of a physiological role in mitochondria.